Tata Kelola Perusahaan dan Atribut Perusahaan pada Ketepatan Pelaporan Keuangan: Bukti dari Perusahaan yang Terdaftar di Bursa Efek Indonesia - Ikbar Pratama (Mahesa Research Center, 2022)
Timeliness and corporate governance are considered important and important factors that affect the usefulness of information available to external users. The purpose of this study was to examine the effects of corporate governance (Size of the Board of Directors and Audit Committee) and company attributes (Company Size) that affect the timeliness of financial reporting of companies listed on the Indonesia Stock Exchange (IDX) in the Republic of Indonesia. The study applied agency theory and formulated four hypotheses that guided the analysis. The study sample consisted of 225 companies registered with the IDX. To achieve the research objectives, the data collected was analyzed using SPSS version 19. The study found a positive but insignificant relationship between company size and financial reporting punctuality, but a negative relationship between board size, audit committee size and corporate sector with financial reporting punctuality. However, the size of the board of directors is insignificant. The study also recommends measures to improve the timeliness of financial reporting on the Indonesia Stock Exchange.